Pengoptimalan Aliran Daya dengan Penambahan Distributed Generation Menggunakan Particle Swarm Optimization - Wati, Trisna; Putra, Muhammad Rizqi (Prosiding Seminar Nasional Teknik Elektro, Sistem Informasi, dan Teknik Informatika (SNESTIK), 2025)
The increasing demand for electrical energy and environmental concerns have encouraged the addition of distributed generation (DG). It has become a relevant solution for managing electrical distribution systems. DG addition does not require network restructuring or configuration, allowing it to be added near consumers located far from the generators. Adding DG to radial network systems can reduce both active and reactive power losses and improve voltage profiles. However, suboptimal DG placement can lead to negative impacts, such as exceeding current limits and harmonic problems in the network system. This research used Particle Swarm Optimization (PSO) to determine the location and DG size in the IEEE 69-Bus radial network system modified to 54-Bus. Compared to other methods, PSO is faster at finding optimal solutions due to its cooperative particle structure and updating. The simulation varied swarm size (1, 5, and 10) with 10 iterations each. The results showed that the optimal solution occurred at different iterations for each swarm size but with the same optimal value. Thus, before DG installation, the active power loss was 2037.71 kW, the reactive power loss was 630.155 kVAR, and the maximum voltage was 4.3186 p.u. After DG installation, the active power loss decreased to 75.2543 kW, the reactive power loss decreased to 11.69819 kVAR, and the maximum voltage decreased to 1.6720 p.u.